2010
DOI: 10.1091/mbc.e09-03-0232
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MYO18A as a Novel Interacting Partner of the PAK2/βPIX/GIT1 Complex and Its Potential Function in Modulating Epithelial Cell Migration

Abstract: MYO18A is found as a novel PAK2 binding partner via βPIX/GIT1. MYO18A-depleted cells showed dramatic changes in shape, actin stress fiber and membrane ruffle formation, and displayed increases in the number and size of focal adhesions and a decrease in cell migration, suggesting an important role of MYO18A in regulating epithelial cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
77
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 54 publications
10
77
1
Order By: Relevance
“…Interestingly, unphosphorylated nonmuscle myosin 2B HMM also gave a 0-nm displacement when interacting with actin in the optical trap (41). The weak F-actin affinity of myosin-18A could still be physiologically significant because this myosin is localized in the lamellipodia of some cells (11,42) where the actin concentration is in the range of 500 M (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, unphosphorylated nonmuscle myosin 2B HMM also gave a 0-nm displacement when interacting with actin in the optical trap (41). The weak F-actin affinity of myosin-18A could still be physiologically significant because this myosin is localized in the lamellipodia of some cells (11,42) where the actin concentration is in the range of 500 M (43).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, our data support the possibility of mammalian myosin-18A providing a tethering activity within the cell, perhaps anchoring other cellular components to the actin cytoskeleton and resisting the strain induced by actively cycling myosin-2 motors within the cell body, or serving as a scaffold for other proteins. In this regard, several studies have identified myosin-18A-associated proteins, such as GOLPH3 (10), myotonic dystrophy kinase-related Cdc4-binding kinase (MRCK) (11) (a kinase that phosphorylates the RLC of myosin-18A), and the PAK2/␤PIX/GITI complex, which are involved in cytoskeletal dynamics and cell motility (42).…”
mentioning
confidence: 99%
“…Recently, it has been shown that myosin-18A␣ is a novel binding partner of the PAK2⅐␤PIX⅐GIT1 complex (13). This suggests that myosin-18A may play an important role in regulating epithelial cell migration.…”
mentioning
confidence: 99%
“…Last, Myo18A was found to co-precipitate with SHP-2, a phosphatase with a key role in NK cell receptors-mediated signaling pathways, 31 and with PAK-2, a serine/threonine kinase that controls the cytoskeletal organization. 27 Of note, SHP-2 has previously been shown to negatively regulate NK cell function, 31 although in other settings, it mediated a positive proliferation signal 34 and activated the IL-1/Erk-mediated cytoskeleton reorganization. 35 Our novel molecular and functional data on a newly described NK cell co-activating receptor have broad potential applications.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Myosin 18A has been shown to play a role in the cytoskeleton organization and to interact with PAK-2 in epithelial cell lines. 27 To further elucidate the mechanisms by which CD245 stimulation increased NK cell degranulation and lysis of target cells that failed to express CD137L, immunoprecipitates were prepared on YT2C2 NK cell line lysates with DY12 or control IgG1 isotype and subjected to electrophoresis and immunoblotting using anti-PAK2 antibody. Whole YT2C2 cell lysate was used as positive control.…”
Section: The Increased Nk Cell Degranulation Mediated Through the Engmentioning
confidence: 99%